Concerted dynamics of metallo-base pairs in an A/B-form helical transition - Olivia P. Schmidt (Nature Portfolio, 2019)
Metal-mediated base pairs expand the repertoire of nucleic acid structures and dynamics. Here, the authors prepared a metallo-DNA duplex including two C-Hg(II)-T base pairs separated by six normal Watson-Crick base pairs and investigated its solution structure and dynamics using NMR spectroscopy.